Determination of veterinary drug residues in food of animal origin: Sample preparation methods and analytical techniques. Issue 17 (7th November 2020) - Li, Shuling; Zhang, Qiongyao; Chen, Mengdi; Zhang, Xuejiao; Liu, Ping
Abstract: Veterinary drugs are widely used in animal husbandry to prevent and treat animal diseases, to promote animal growth, and to improve the conversion rate of feed. However, the use of veterinary drugs in food-producing animals may leave residues of the parent compounds, and/or their metabolites in food products resulting in harmful effects to humans. To ensure food safety, sensitive and effective analytical methods have been developing rapidly. So it is necessary to make a systematic summary of detection methods of veterinary drug residues. Sample preparation methods and analytical techniques are the two main parts of analyzing veterinary drug residues which were described in detail. Sample preparation methods, such as solid-phase extraction, liquid–liquid extraction, immunoaffinity chromatography, and QuEChERS, were summarized by the specific examples. The three types of methods, microbial, immunological, and physicochemical methods, for screening or determination were described, including microbial inhibition, enzyme-linked immunosorbent assay, colloidal gold immunoassay, fluorescence polarization immunoassay, biosensor technology, application of quantum dots, capillary electrophoresis, liquid chromatography, and liquid chromatography-mass spectrometry. In addition, the advantages and shortcomings of methods were also described. The challenges and prospects were discussed for the analysis of veterinary drug residues in animal-derived foods. Graphical Abstract: